Flow and engagement: different degrees of the same? - Rupayana, Disha Deepak (Kansas State University, 2008)
The present study focused on empirically assessing the differences between the two flow models (FSS-II; Jackson & Eklund, 2002; WOLF, Bakker, 2005) and then their similarity or difference with the Schaufeli (2002) model of engagement. Using a 2nd order factor analysis it was found that FSS-II and WOLF measured different conceptualizations of flow while engagement as measured by the UWES did not differentiate from the flow experience. Implications and directions for future research were discussed.
Keywords: flow; engagement; Psychology, Industrial (0624)